Предмет: Математика, автор: asylbekaizhan8385

Есепте:

92 – (52 ⋅ 1 + 32 ⋅ 0) =

62 + 22 ⋅ 3 + 52 =

82 – (92 ⋅ 0 + 72) + 42 =

Артқа

Тексеру


Ответы

Автор ответа: rasulserikuly
5

Ответ:

1)40

2)180

3)52

Пошаговое объяснение:

92 – (52 ⋅ 1 + 32 ⋅ 0) =92—(52+0)=92—52=40

62 + 22 ⋅ 3 + 52 =62+66+52=128+52=180

82 – (92 ⋅ 0 + 72) + 42 =82—(0+72)+42=82—72=10+42=52


asylbekaizhan8385: дурыс емес
asel160711: Дурыс емес
Автор ответа: iramazurk
2

Ответ:

Пошаговое объяснение:

1.

1) 52*1 + 32*0 = 52

2) 92 - 52 = 40

2.

62 * 22*3 + 52 = 62 + 66 + 52 = 180

3.

1) 92 * 0 + 72 = 72

2) 82 - 72 + 42 = 52


asylbekaizhan8385: дурыс емеской
asel160711: Дурыс емес
Ramina2404: неше болат???
timurzhanaev1: кандай ответь
Похожие вопросы